Toxicity to and egg‐laying avoidance of Drosophila suzukii (Diptera: Drosophilidae) caused by an old alternative inorganic insecticide preparation. Issue 4 (1st December 2017) - Andreazza, Felipe; Vacacela Ajila, Henry E; Haddi, Khalid; Colares, Felipe; Pallini, Angelo; Oliveira, Eugênio E
Abstract: BACKGROUND: The application of synthetic insecticides remains the most used tool for the management of spotted‐wing drosophila, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae). However, management of this pest in the organic production of soft‐skinned fruits is a complex task due to the restricted number of registered products. Here, we assess the toxicity of lime sulfur and evaluate whether lime sulfur‐treated strawberry plants affected the oviposition and development of D. suzukii . RESULTS: Lime sulfur exhibited adequate toxicity to D. suzukii (LC50 = 26.6 mL L −1 ) without phytotoxicity to strawberry plants. When D. suzukii females were exposed to lime sulfur‐treated plants in no‐choice bioassays, oviposition was significantly ( t ‐test, P < 0.05) reduced compared with that on untreated plants. In free‐choice bioassays, D. suzukii females laid significantly (paired t ‐test, P < 0.05) more eggs on untreated plants. Furthermore, in the free‐choice bioassays, immature development was slower for adults that originated from eggs laid on lime sulfur‐treated plants than from those laid on untreated plants. CONCLUSIONS: Lime sulfur showed adequate control and, therefore, has potential for use as a management tool against D. suzukii infestations in organic production systems. This old, alternative insecticide preparation not only caused adult fly mortality, but also reduced the number of eggs laid on lime sulfur‐treated plants. © 2017 Society of Chemical Industry Abstract : The present investigation assessed the toxicity of an old, alternative insecticide preparation (i.e., lime‐sulfur) and evaluated whether lime‐sulfur‐treated strawberry plants affected the oviposition and development of Drosophila suzukii .